Pengaruh Kesadaran, Pengetahuan Perpajakan, Kualitas Layanan dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak - Amelia Robbi Anisa; Endang Masitoh Wahyuningsih; Sari Kurniati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
As one of the largest sources of revenue, tax collection is one of the government's focuses for the smooth running of national development activities. The thing that can provide a significant increase in tax revenue is all compliant taxpayers. The purpose of this finding is to examine the impact of tax awareness, tax knowledge, service quality, and tax sanctions on taxpayer compliance. The data source that is realized is primary data obtained by researchers from the results of distributing questionnaires. The population in this finding is all Taxpayers of the Tax Consultant Office in Surakarta. The sample of this finding is 100 respondents of clients of the PIK Surakarta Tax Consultant Office in 2024 which was determined using the Accidental Sampling technique. The data analysis method in this finding applies multiple regression analysis processed with the SPSS version 25 program. The results of this finding indicate that tax awareness and tax sanctions have an effect on taxpayer compliance, while tax knowledge and service quality do not have an effect on taxpayer compliance.